A small two-stage pulse tube cryocooler operating at liquid Helium temperatures with an input power of 1 kW. (December 2017) - Schmidt, B.; Vorholzer, M.; Dietrich, M.; Falter, J.; Schirmeisen, A.; Thummes, G.
Highlights: A 4 K GM-type two-stage pulse tube cooler with low input power was developed. The cooler was optimized for low noise, low vibration cooling of superconducting sensors. No-load temperatures of 44.4 K and 2.36 K on the first and second stage respectively were reached. The cooler provided a cooling power of 72 mW at 4.2 K and 150 mW at 5.0 K. Abstract: The development of 4 K two-stage pulse tube cryocoolers (PTCs) is commonly aimed at high cooling powers in order to compete with GM-cryocoolers. However, more sensitive applications still suffer from intrinsic disturbances of the cryocooler. To address this issue, the development of PTCs with small cooling powers is essential for sensitive measurements. Here we report the development of a new two-stage GM-type PTC, designed to work with a commercial Helium compressor with only 1 kW electric input power. The pressure and mass flow oscillation is generated by means of a remote rotary valve. The PTC was modeled for the operation at temperatures near 5 K with the simulation environments SAGE and REGEN. A first prototype was fabricated, operated and optimized in a test cryostat. Up to now, the PTC reaches a minimum temperature of 2.36 K and provides a cooling power of 72 mW at 4.2 K and 120 mW at 5 K. This cooling power is sufficient for small cryoelectronic devices like single photon detectors, transition-edge bolometers or low-noise Nb-SQUIDs (superconducting quantum interference devices).